2014
DOI: 10.1155/2014/284161
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Inflation Uncertainty with Structural Breaks Case of Turkey (1994–2013)

Abstract: In recent years, the importance attached to the concept of volatility has increased and become a phenomenon frequently encountered in every field ranging from financial markets to macroeconomic indicators. In this study, inflation data obtained from CPI index for the period of 1994:01–2013:12 in Turkey was used to determine the best representative of the inflation uncertainty. To realize this, both symmetric and asymmetric GARCH-type models were employed. Since there are many factors that may lead to structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Similarly, Göktaş and Dişbudak (2014) Bai andPerron (1998, 2003) extended the Quandt-Andrews test by allowing for multiple unknown breakpoints, which is the structural break test we use in our analysis. However, we also need to test for potential breakpoints in the variance.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Göktaş and Dişbudak (2014) Bai andPerron (1998, 2003) extended the Quandt-Andrews test by allowing for multiple unknown breakpoints, which is the structural break test we use in our analysis. However, we also need to test for potential breakpoints in the variance.…”
Section: Methodsmentioning
confidence: 99%
“…However, we also need to test for potential breakpoints in the variance. Consequently, similar to Göktaş and Dişbudak (2014), the squared residuals of the AR models are regressed on a constant, and Bai-Perron tests are then reperformed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These researchers also indicated that the break point was in 1985; the beginning of the Great Moderation period and other macro variables stabilised inflation and its aftermath on relative prices across US cities. On the other hand, [10] studied the concept of volatility and uncertainty in inflation using CPI index for the period of 1994 until 2013 in Turkey. Using Bai-Perron test, two different break points in terms of mean and variance were identified, namely February 2002 and June 2001.…”
Section: Introductionmentioning
confidence: 99%